1968
DOI: 10.1071/bt9680469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate salinity on growth and on submicroscopic structure of leaf cells of Atriplex halimus L

Abstract: For optimal growth Atriplex halimus requires slight salinization of the growth substrate. It tolerates higher salt concentrations, but concentrations above 14 atm retard growth. At 9-14 atm, changes in the submicroscopic structure of leaf cells occur, viz. swelling of chloroplasts and mitochondria, appearance of numerous large lipid droplets, swelling of the nuclear membranes, extensive vacuolization, and distortion of the tonoplast with formation of numerous myelin bodies. There is no fundamental difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
4
11
0
Order By: Relevance
“…The concentrations of 10% or 25% seawater at 21 days post-anthesis in Gemmieza-9 caused pronounced swelling of the thylakoid membranes in chloroplasts. These results coincided with those obtained, in case of plants grown in high salinity treatments, such as Atriplex halimus [28] wheat [29] and Mesembryanthemum crystallinum [30].…”
Section: Discussionsupporting
confidence: 77%
“…The concentrations of 10% or 25% seawater at 21 days post-anthesis in Gemmieza-9 caused pronounced swelling of the thylakoid membranes in chloroplasts. These results coincided with those obtained, in case of plants grown in high salinity treatments, such as Atriplex halimus [28] wheat [29] and Mesembryanthemum crystallinum [30].…”
Section: Discussionsupporting
confidence: 77%
“…All these factors would decrease the carboxylation capacity of Rubisco and ATP synthesis (Lawlor and Cornic, 2002), and subsequently the photosynthetic capacity of trees in the hypersaline site (Sobrado and Ball, 1999). High salinity induced changes, observed here for A. marina in the hypersaline site, were likewise reported for herbaceous Atriplex halimus (Blumenthal-Goldschmidt and Poljakoff-Mayber, 1968;Kelly et al, 1982), Aeluropus littoralis (Barhoumi et al, 2007) and rice (Mitsuya et al, 2000;Rahman et al, 2002;Yamane et al, 2003). Decreases in CO 2 exchange at hypersalinity observed in this study are similar to those reported for A. marina in Australia (Sobrado and Ball, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…Many of the deleterious effects of Na+, however, seem to be related to the structural and functional integrity of membranes. Swelling, distortion, and other structural changes have been observed in various membranes ofsalt-stressed plants, and the plasmalemma has been shown to lose its selective permeability (4,13,27). Sodium also inhibits K+ and Ca2+ uptake in salt-stressed cotton roots (5).…”
mentioning
confidence: 99%